145k views
0 votes
The graph below shows a translation of preimage triangle vertex C to image triangle vertex C'.

What is the algebraic rule for this translation?
A. (x,y) = (x+6,9+2)
B. (x,y) → (x-6,y-2)
C. (x,y) → (x -6,y-6)
D. (x,y) → (x+2,x+10)

The graph below shows a translation of preimage triangle vertex C to image triangle-example-1

2 Answers

0 votes

Answer:

it is B

Explanation:

User Drowny
by
5.2k points
5 votes

Answer:

Option (B)

Explanation:

From the figure attached,

Triangle with vertex C' is a translated form of the triangle with vertex C.

Coordinates of pre-image C → (2 , 6)

Coordinates of the image C' → (-4, 4)

Rule followed from pre-image C to image C',

(2, 6) → (-4, 4)

(2, 6) → [(2 - 6), (6 - 2)]

(x, y) → [(x - 6), (y - 2)]

Therefore, rule given in option (B) is the answer.

User Sushovan Mandal
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.